The importance of the formulation in the effectiveness of Coenzyme Q10 supplementation in mitochondrial disease therapy - Lucangioli, Silvia Edith (2012)
This report describes the response of a patient treated with two different coenzyme Q10 extemporaneous pharmaceutical formulations that generated radical changes in her symptoms and life quality. It could explain why in some cases therapy with coenzyme Q10 does not work in patients with deficiency of this coenzyme. It is important that the scientific community dedicated to the area of health be aware and mindful of differences that can occur in extemporaneous preparations which are not as strict at the time of development and control as in pharmaceutical industry. The aim of this study was to demonstrate the need for extreme control in the coenzyme Q10 formulation administered to patients.